2017
DOI: 10.18632/oncotarget.23678
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of PD-1 inhibitors in non-small cell lung cancer (NSCLC) patients of different ages

Abstract: BackgroundImmunosenescence, the age-related decline of immunity, affects the immune responses of non-small cell lung cancer (NSCLC) patients. Through immune responses, programmed death-1 (PD-1) inhibitors exert their antitumor robustness. In different ages of NSCLC patients, especially the older patients, the effectiveness of PD-1 inhibitors remains unclear. It is still controversial whether pembrolizumab or nivolumab should be used in treating NSCLC patients.Results2,192 NSCLC patients from four phase III RCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
(33 reference statements)
1
18
1
1
Order By: Relevance
“…We also showed that IO-chemotherapy significantly improved OS both in patients < 65 years old (HR 0.46; P < .001) and ≥ 65 years old (HR 0.69; P = .008), with greater benefit in in younger patients (interaction P = .038). This finding is different from previous meta-analyses which revealed similar efficacy with immune checkpoint inhibitor monotherapy in patients younger vs. older than 65 years old [31, 32]. These results are clinically relevant because a majority of lung cancer patients were diagnosed at older ages and were often with poor performance status in real world [33].…”
Section: Discussioncontrasting
confidence: 84%
“…We also showed that IO-chemotherapy significantly improved OS both in patients < 65 years old (HR 0.46; P < .001) and ≥ 65 years old (HR 0.69; P = .008), with greater benefit in in younger patients (interaction P = .038). This finding is different from previous meta-analyses which revealed similar efficacy with immune checkpoint inhibitor monotherapy in patients younger vs. older than 65 years old [31, 32]. These results are clinically relevant because a majority of lung cancer patients were diagnosed at older ages and were often with poor performance status in real world [33].…”
Section: Discussioncontrasting
confidence: 84%
“…Despite improvements in therapeutic strategies, the survival and outcome of patients with NSCLC have not been markedly affected ( 4 ). The majority of patients have progressed to the advanced stage of the disease when the diagnosis is confirmed, which is beyond the optimal treatment period ( 18 ). Therefore, it is essential to elucidate the pathogenesis of NSCLC and to identify novel treatment targets.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, using ICIs that block the cross talk of PD-L1 molecules and PD-1 molecules may inhibit tumor cells from evading the immunoreaction under this situation. Latest studies reveal that the efficacy of PD-1/PD-L1 inhibitors may correlate with sex and age; 4 , 5 however, little is known whether it is associated with the status of smoking.…”
Section: Introductionmentioning
confidence: 99%